Ischemic Stroke With Atrial Fibrillation: Characteristics and Time Trends 2006 to 2017 in the Dijon Stroke Registry. Issue 6 (20th April 2021) - Gabet, Amélie; Guenancia, Charles; Duloquin, Gauthier; Olié, Valérie; Béjot, Yannick
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Because of the aging population, an increase in the prevalence of atrial fibrillation (AF) is currently observed, thus leading to a rise in AF-related ischemic stroke (IS). We analyzed the current prevalence of AF among patients with IS, their characteristics, and temporal trends from 2006 to 2017 in the population-based Dijon Stroke Registry. Methods: We used data from the Dijon Stroke Registry, an ongoing population-based study that records all cases of acute stroke among residents of the city of Dijon. All patients with IS between 2006 and 2017 were included. Previous AF was defined if it was mentioned in the medical file before stroke and newly diagnosed AF if it was diagnosed during the diagnostic workup of patients with acute stroke. Results: During the period 2014 to 2017, among the 796 patients with IS recorded in the Dijon Stroke Registry, 239 (30.0%) had AF, of whom 79 (9.9% of total patients with IS) had newly diagnosed AF, and 98 (12.3%) had previous AF treated with oral anticoagulants. Patients with IS with AF had more disabilities and a higher initial severity according to the National Institutes of Health Stroke Scale compared with those without AF. The age-adjusted prevalence of AF in patients with IS increased between 2006 and 2017 (+9% per time period), with an important increase in men aged 65 to 74 years (+81%) and women aged ≥85 years (+24%), and a significant decrease in women aged 65 to 74 years (−39%). The use of oral anticoagulant treatment in previous AF patients increased between 2006 and 2009 and 2014 and 2017 (29.3% to 61.3%, P <0.0001). However, 37.5% of patients with previous AF and CHADS2 score ≥2 were not treated with OAC. Conclusions: The increase in AF prevalence in patients with IS could be related to a better diagnosis of this condition. The underuse of oral anticoagulation treatment was still observed.